Key motor and non-motor features in early dementia with Lewy bodies - Planas-Ballvé, Anna; Rios, José; Ispierto, Lourdes; Gea, Mireia; Grau, Laia; Jiménez, Marta; Cáceres, Cynthia; Martínez, Sílvia; Beyer, Katrin; Álvarez, Ramiro; Pastor, Pau; Vilas, Dolores (Frontiers in Neurology, 2025)
ObjectiveThe objective of our study was to characterize early-stage dementia with Lewy bodies (DLB) focusing on motor and non-motor symptoms.MethodsThis cross-sectional study prospectively included newly diagnosed DLB patients within 3 years of cognitive symptom onset. Comparisons were made with individuals with Parkinson’s disease (PD), Alzheimer’s disease (AD), and controls. Demographic and clinical data were collected, and motor and non-motor symptoms were assessed using structured interviews and validated scales and questionnaires.ResultsA total of 107 participants were included (23 DLB, 27 PD, 26 AD, and 31 controls). DLB patients (median age 75 years, median disease duration since diagnosis 2 months) commonly reported motor symptoms, including gait disturbances (91.3%), tremor (73.9%), and bradykinesia (87%), with tremor being predominantly unilateral (76.5%) and action-type (52.9%). The most frequent motor subtype was akinetic-rigid (52.2%). Motor symptoms were similar to PD, except for more frequent falls (34.8% vs. 11.1%, p = 0.044) and gait disturbances in DLB patients (91.3% vs. 63%, p = 0.019). Non-motor symptoms, particularly visual hallucinations and neuropsychiatric symptoms were more prevalent in DLB than in PD, while sleep and autonomic symptoms were similar. An abnormal orthostatic test was more frequent in DLB than in PD (45.5% vs. 11.5%, p < 0.008). Compared to AD, all non-motor symptoms were significantly more frequent in DLB. Finally, DLB patients had lower functional independence and quality of life than both PD and AD (p < 0.0001).ConclusionEarly-stage DLB closely resembles PD in motor symptoms but has more neuropsychiatric non-motor symptoms compared to PD and overall non-motor symptoms than AD.